Challenges and prospects for developing genetic resistance in common wheat against stem rust in Western Siberia - Kelbin, V. N.; Skolotneva, E. S.; Salina, E. A. (Vavilovskiĭ zhurnal genetiki i selekt͡s︡ii, 2020)
Current studies on bread wheat resistance to stem rust have two main subjects: complex analysis for resistance of bread wheat germplasm using molecular markers, field screening and laboratory tests against samples of different fungal populations, and searching for sources and donors of new genes and gene loci, including cultivated and wild relatives of wheat. To achieve adequate genetic control of the disease, an integral approach is important, incorporating both data on sources of resistance and relevant information on pathogenic populations existing in the region, their race composition and dynamics of virulence genes. The analysis of experimental data on field screening of bread wheat varieties from the CIMMYT nursery germplasm for stem rust resistance in the Omsk and Novosibirsk regions, together with laboratory testing of infection samples on the international set of wheat differential lines, suggests that a separate “Asian” population of Puccinia graminis f. sp. tritici exists in Western Siberia and the Altai Territory. Wheat resistance genes Sr2, Sr6Ai#2, Sr24, Sr25, Sr26, Sr31, Sr39, Sr40, Sr44, and Sr57 are of practical interest for advanced wheat breeding programs for stem rust immunity in Western Siberia. This review provides an analysis of the gene sources that remain effective against the West Siberian population of P. graminis, in order to facilitate the initial stage of selection of breeding material to develop a stable genotype by gene pyramiding. The basic requirements for conducting a phytopathological test of breeding material are presented. A list of molecular markers for the mentioned resistance genes, both widely used in marker-assisted selection and requiring verification, has been compiled.